Iraq and terrorism: How are "rogue states" and terrorists connected? - Ulrich Schneckener (Stiftung Wissenschaft und Politik (SWP), 2003)
Even after U.S. Secretary of State Colin Powell's presentation to the UN Security Council on 5 February 2003, doubts remain whether a connection exists between Saddam Hussein and al-Qaeda. However, the public focus on this question largely overlooks the fact that the U.S. government's threat analysis concentrates more on systematic rather than specific links between 'rogue states' and terrorists. For the U.S. government, a potential war against Iraq represents an integral component of the international fight against terrorism. In this respect, the Bush administration differs significantly from governments in Europe and the Arab world that differentiate more clearly between the challenges posed by Iraq and international terrorism. These governments fear that a war against Iraq would itself serve as a catalyst for the spread of terrorism and the creation of links between the Iraqi regime and terrorist groups such as al-Qaeda. Yet how plausible are these positions? What supports or undermines the thesis that 'rogue states' are linked to terrorists? (SWP Comments / SWP)
Keywords: 320